Phytomedicine: An abundant source of safe and efficacious therapeutics to revive local pharmaceutical production: Phytomédecine: Une source abondante de thérapeutiques sûres et efficaces pour relancer la production pharmaceutique locale - Emeje, Martins; Olorunsola, Emmanuel (West African Journal of Pharmacy, 2026)
Background: Many health systems largely depend on phytomedicines. However, these therapeutic agents are being criticized because of the limited information on their quality, safety and efficacy. Objectives: This review aimed to aggregate scientific evidence on the availability, safety and efficacy of phytomedicines, to reveal the available methods for optimizing their quality and to intensify the need for their local production. Methods: About 1000 peer reviewed articles from 5 databases (Google scholar, Pubmed, Scopus, Web of Science and Science direct) were reviewed to extract relevant information on this subject of discussion. Results: Over 50,000 plant species are known to occur in sub-Saharan Africa alone; and over 5,000 plants are already known to be used for medicinal purposes in Africa, but only a few have been adequately studied. African countries and institutions, including researchers have continued to document medicinal plants of importance as knowledge grows and new information emerge. Phytomedicines are known to be useful in managing many diseases but there are challenges of standardization, formulation and safe use in some instances. There are now several ways of addressing these challenges. Conclusion: It is clear that our health system largely depends on traditional medicines and the world is returning to nature. Africa is rich in medicinal plants and the medicinal components can be converted to suitable dosage forms; hence, an enhanced production of phytomedicines could revive local pharmaceutical production. Résumé Contexte: De nombreux systèmes de santé dépendent largement des phytomédicaments. Cependant, ces agents thérapeutiques font l’objet de critiques en raison du manque d’informations sur leur qualité, leur innocuité et leur efficacité. Objectifs: Cette étude vise à rassembler les données scientifiques sur la disponibilité, l’innocuité et l’efficacité des phytomédicaments, à mettre en évidence les méthodes disponibles pour optimiser leur qualité et à souligner la nécessité de relancer leur production locale. Méthodes: Environ 1 000 articles évalués par des pairs provenant de 5 bases de données (Google Scholar, Pubmed, Scopus, Web of Science et Science Direct) ont été examinés afin d’extraire les informations pertinentes sur ce sujet de discussion. Résultats: On recense plus de 50 000 espèces végétales rien qu’en Afrique subsaharienne, dont plus de 5 000 sont déjà utilisées à des fins médicinales. Cependant, seules quelques-unes ont fait l’objet d’études approfondies. Les pays et institutions africains, notamment les chercheurs, ont continué à répertorier les plantes médicinales importantes à mesure que les connaissances s’enrichissent et que de nouvelles informations émergent. Les phytomédicaments sont reconnus pour leur utilité dans la prise en charge de nombreuses maladies, mais des difficultés subsistent en matière de standardisation, de formulation et d’utilisation sans risque dans certains cas. Il existe désormais plusieurs moyens de relever ces défis. Conclusion: Il est clair que notre système de santé repose en grande partie sur les médecines traditionnelles et que le monde se tourne à nouveau vers la nature. L’Afrique regorge de plantes médicinales dont les composants actifs peuvent être transformés en formes galéniques appropriées ; ce qui souligne la nécessité de relancer la production locale de phytomédicaments.